PENERAPAN MODEL CREATIVE PROBLEM SOLVING MENGGUNAKAN TEKNIK PROBING PADA PEMBELAJARAN MATEMATIKA - Sospolita, Nadya; Sukasno, Sukasno; Fitriyana, Nur (LPPM STKIP PGRI Bandar Lampung, 2020)
This research is motivated by the low learning outcomes of mathematics and the lack of active students in the learning process in class. This study aims to determine the completeness of student learning outcomes after participating in learning using the Creative Problem Solving model using Probing techniques, as well as to describe student learning activities during the learning process. The type of research used is in the form of Pre Experimental Design. The population is all grade VII students of SMP Negeri 2 Lubuklinggau in the 2018/2019 academic year and the sample is grade VII.12 students with 29 students. Data collection is done by testing and observation techniques. The collected data were analyzed using t-test at a significant level Î± = 0.05. Based on the results of data analysis, it can be concluded that the mathematics learning outcomes of Grade VII students of SMP Negeri 2 Lubuklinggau after applying the Creative Problem Solving model using the Probing technique are significantly completed. The average final test score is 83.0 and the percentage of students who complete reaches 75.9%. The average score of student learning activities has increased ateach learning meeting.